Flavored Guilu Erxian decoction inhibits the injury of human bone marrow mesenchymal stem cells induced by cisplatin - Ke, Bin; Shi, Lin; Xu, Zhaozhong; Wu, Gang; Gong, Yuxin; Zhu, Lixia; Wang, Yanjing; Ouyang, Huailiang; Wang, Xilong (Cellular and Molecular Biology, 2018)
To examine the exact role of flavored Guilu Erxian decoction, a Traditional Chinese Medicine (TCM) in the treatment of cisplatin-induced side-effects in bone marrow mesenchymal stem cells (BM-MSCs). BM-MSCs were isolated from bone marrow collected from SD rats and identified by flow cytometry. Cells were cultivated in MEM alpha medium containing 5% (TCM-L), 10% (TCM-M) and 20% (TCM-H) dosages of flavored Guilu Erxian decoction with or without cisplatin. Cell viability was determined through CCK-8 and thymidine analog 5-ethynyl-2"²-deoxyuridine (EdU) staining assay. Flow cytometry was used to determine cell cycle and apoptosis. The expression of p21 and cleaved-caspase-3 were examined using Western blot assay. The PI3K-AKT-mTOR pathway associated proteins, including p-PI3K, p-AKT and p-mTOR, were also examined by Western blot assay. CCK-8 and EdU staining assay demonstrated that cisplatin could inhibit cell proliferation in BM-MSCs in a dose and time dependent manner. Further, cisplatin could induce apoptosis through increasing G0/G1 cell cycle arrest, p21 and cleaved-caspase-3 expression. However, these phenomena would be significantly alleviated when adding the serum containing flavored Guilu Erxian decoction. Furthermore, the PI3K-AKT-mTOR pathway activation could be inhibited by cisplatin in BM-MSCs, while flavored Guilu Erxian decoction treatment successfully abrogated this effect. Combination of flavored Guilu Erxian decoction and cisplatin could reduce the damage to BM-MSCs. This indicates that the flavored Guilu Erxian decoction can enhance the possibility of BM-MSCs repairing and rehabilitating the normal function of injured tissues induced by cisplatin, which could provide a new direction for therapeutic applications.